O-034 Ban the scan: clinical utility of routine computed tomography of the head following elective neuroendovascular interventions. (23rd July 2022) - Barros, G; Meyer, R; Bass, D; Nistal, D; McAvoy, M; Clarke, J; Vanent, K; Cruz, M; Levitt, M
Abstract : Introduction/Purpose: Routine imaging after elective neurosurgical procedures is common practice at many institutions. However, recent literature suggests there is little evidence to support this in patients with unchanged postoperative neurologic examinations. This has been demonstrated in patients undergoing craniotomy for brain tumors, microsurgical clipping and endovascular coiling of unruptured aneurysms, endoscopic skull base tumor resections, and ventriculoperitoneal shunts. Our objective is to assess the clinical utility of routine computed tomography of the head (CTH) following a broad range of elective neuroendovascular interventions. Materials and Methods: A retrospective review was performed on patients who underwent neuroendovascular interventions between 2011–2021 at a single institution. Patients with acute hemorrhage, pre-surgical embolization for resection of tumors or arteriovenous malformations, and patients missing postprocedural CTH were excluded. Results: Of 509 procedures identified, 354 were eligible for analysis. Procedures performed included coiling, stent-assisted coiling, and flow-diverting stents for unruptured cerebral aneurysms; embolization of arteriovenous malformations/fistulas; middle meningeal artery embolization; carotid artery stenting; and venous sinus stenting. There were 17 patients (4.8%) with abnormal findings on postprocedural CTH ( figure 1 ). Nine patients with abnormal postprocedural CTH had intraprocedural complications and/or new postprocedural neurologic deficits that would prompt imaging regardless of institutional practice. Of the remaining eight (2.3% of total) patients with unexpected findings on postprocedural CTH, none required additional procedures or major changes in clinical care. New postprocedural neurologic deficit was the only significant predictor of an abnormal routine CTH (OR 6.79, CI 2.01–20.32, p=0.0009) in univariate analysis ( table 1 ). Conclusions: In a large cohort of patients who underwent elective neuroendovascular intervention, we did not identify a patient in whom a routine postprocedural CTH alone meaningfully altered the course of clinical care. Any CTH that facilitated a change in care would likely have been triggered by a known intraprocedural complication or a new postprocedural neurological deficit. Routine CTH may not be necessary after uncomplicated elective neuroendovascular intervention when combined with careful postprocedural neurological assessment. Disclosures: G. Barros: None. R. Meyer: None. D. Bass: None. D. Nistal: None. M. McAvoy: None. J. Clarke: None. K. Vanent: None. M. Cruz: None. M. Levitt: 1; C; Stryker, Medtronic. 2; C; Medtronic, Metis Innovative. 4; C; Synchron, Cerebrotech, Proprio, Hyperion Surgical.